The Influence of Social Media on the Quality of Interpersonal Relationships in Adolescents in Indonesia - Budiawan, Budiawan; Myint, Aung; Hlaing, Nandar (World Psychology, 2025)
The advent of social media has transformed the way adolescents communicate and interact with one another. While social media provides a platform for social connection, its influence on the quality of interpersonal relationships, particularly among adolescents, remains a critical area of study. In Indonesia, where social media usage among adolescents is high, understanding its impact on relationships is crucial for promoting healthy social interactions. This study investigates the influence of social media on the quality of interpersonal relationships in adolescents in Indonesia. The research utilizes a mixed-methods approach, combining quantitative surveys and qualitative interviews with 300 adolescents aged 12-18 years. The survey measured the frequency of social media use and the perceived quality of relationships with family, friends, and peers. The qualitative interviews provided deeper insights into adolescents’ experiences with social media and its role in shaping their social interactions. The results indicate that excessive social media use is associated with lower quality in face-to-face interactions, leading to weaker emotional bonds with family and friends. However, moderate use of social media was linked to enhanced peer connections and better communication skills. The study concludes that social media can both positively and negatively affect interpersonal relationships, and suggests that balanced usage should be encouraged to foster healthier social dynamics.